ANALYSIS OF EFL STUDENTS’ CITATION PRACTICES AND PROBLEMS IN ACADEMIC WRITING - Rezeki , Yanti Sri (International Journal of Educational Best Practices, 2018)
Citing sources correctly is vital in academic writing including research proposals. Despite its significance, students seem to perform it poorly  due to lack of knowledge and awareness of its role in their writing. As the result, they are often accused of committing plagiarism. One of the ways to prevent students from committing plagiarism is by providing them with sufficient  knowledge and skills related to proper citations. This study is a preliminary effort to identify student citation practices within the English Education department of a state university in West Kalimantan, Indonesia. Employing qualitative content analysis, the researcher examined samples of students’  proposals to describe the ways in which citations were written and the common problems that occurred. The findings suggest that students mostly cited as non integral/non-reporting. The study also reveals that students’ most common  mistakes in the citation are found in language and content. The study concludes with the need to provide students with clear guidelines for citation and strong remarks on plagiarism.